Repeatability of Central and Peripheral Pulse Wave Velocity Measures: The Atherosclerosis Risk in Communities (ARIC) Study - Meyer, Michelle L; Tanaka, Hirofumi; Palta, Priya; Patel, Mehul D; Camplain, Ricky; Couper, David; Cheng, Susan; Al Qunaibet, Ada; Poon, Anna K; Heiss, Gerardo (American journal of hypertension, 2016)
Arterial stiffness measures are emerging tools for risk assessment and stratification for hypertension and cardiovascular disease (CVD). Carotid-femoral pulse wave velocity (cfPWV) is an established measure of central arterial stiffness. Other measures of PWV include femoral-ankle (faPWV), a measure of peripheral stiffness, and brachial-ankle PWV (baPWV), a composite measure of central and peripheral stiffness. Repeatability of central, peripheral, and composite PWV measures has not been adequately examined or compared. Participants (n = 79; mean age 75.7 years; USA) from a repeatability study nested within the Atherosclerosis Risk in Communities (ARIC) Study visit 5 (2011-2013) underwent 2 standardized visits, 4-8 weeks apart. Trained technicians obtained 2 PWV measurements at each visit using the VP-1000 Plus system. We calculated the intraclass correlation coefficient (ICC), SE of measurement, and minimal detectable change (MDC95; 95% confidence interval) and difference (MDD). The ICCs and 95% confidence intervals (95% CIs) were 0.70 (0.59, 0.81) for cfPWV, 0.84 (0.78, 0.90) for baPWV, and 0.69 (0.59, 0.79) for faPWV. The MDC95 between repeat measures within an individual was 411.0 cm/s for cfPWV, 370.6 cm/s for baPWV, and 301.4 cm/s for faPWV. The MDD for 2 independent samples of 100 per group was 139.3 cm/s for cfPWV, 172.3 cm/s for baPWV, and 100.4 cm/s for faPWV. Repeatability was acceptable for all PWV measures in a multicenter, population-based study of older adults and supports its use in epidemiologic studies. Quantifying PWV measurement variation is critical for applications to risk assessment and stratification and eventual translation to clinical practice.